Ca2+ signal contributing to jasmonic acid‐induced direct and indirect defense against the whitefly Bemisia tabaci in tomato plants. Issue 9 (18th July 2021) - Liu, Xin; Hussain, Sabir; Xie, Wen; Guo, Zhaojiang; Wu, Qingjun; Wang, Shaoli; Liu, Yong; Zhang, Youjun
Abstract: The phytophagous whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) causes serious crop yield losses around the world especially by vectoring viruses. Exogenous jasmonic acid (JA) induces direct plant resistance to B. tabaci, but the underlying mechanism of JA‐induced exogenous defenses is not well understood. Here, we demonstrate that exogenous JA not only increases the cytosolic Ca 2+ concentration ([Ca 2+ ]cyt ) in tomato mesophyll cells but also induces the expression of Ca 2+ ‐sensor genes and plant defense genes. Pre‐treatment with Ca 2+ inhibitor (ruthenium red) significantly repressed the elevation of [Ca 2+ ]cyt, expression of JA‐induced genes, and emission of plant volatiles induced by JA, thus reducing the JA‐induced direct (feeding choice and fitness of B. tabaci ) and indirect [olfactory choice and parasitism by the parasitoid Encarsia formosa Gahan (Hymenoptera: Aphelinidae)] plant resistance to B. tabaci . These results indicate that the Ca 2+ signal induced by JA mediates and directs the plants defenses against whitefly. Present results will not only give us a better understanding of how exogenous JA influences the crop community, but also deliver some clues for the potential application of exogenous JA, as a plant elicitor, in whitefly management. Abstract : Exogenous jasmonic acid (JA) can induce defenses against the whithefly Bemisia tabaci (Hemiptera: Aleyrodidae) in tomato plants, not only by directly decreasing the attraction and performance of the whitefly, but also by indirectly increasing the attraction and parasitism of the parasitoid wasp Encarsia formosa (Hymenoptera: Aphelinidae). Moreover, a calcium signal induced by JA mediates and orients these plant defenses against whitefly. JA can act as a plant elicitor which enhances the defense against whitefly.